Perceived Status of CFR Practices Among Investors and Managerial Employees - Vethirajan, C.; Banupriya, K. (Indian Journal of Finance, 2018)
Corporate financial reporting is of great significance to accomplish financial accounting objectives as well as to contribute to the efficient allocation of resources through healthy economic decisions. The disclosure of accounting practices have developed in accordance with the changing economic, political, technological, and social environments to fulfil the objectives of financial reporting. There are two major types of corporate disclosures : (a) mandatory disclosure and (b) voluntary disclosure. Reporting mandatory disclosure is compulsory as per laws and regulations, and disclosure which is not compulsory, but recommended to be disclosed with mandatory reports, is said to be voluntary. In the present study, a total of 435 investors and 150 managerial employees were selected as the sample size for the study. Simple random sampling technique was used for investors, and judgmental sampling technique was used for managerial persons. The statistical tools used for the analysis were univariate one-way ANOVA and multivariate discriminant analysis. Univariate ANOVA was used to identify the significance of the differences in the levels of perception between the two groups. This test was preferred over t - test (as there were two respondent groups) as test ofÂ equality of group means is a pre-requisite for running discriminant analysis. The discriminant analysis was used to identify the variables that were important in group separation. It was concluded that CFR was important for investors, and disclosure status of most of the mandatory and voluntary items in corporate annual reports was good, but with significant differences in such opinion levels between the two groups, which may be attributed to inconsistency in the disclosures.